Google Sites–Assisted Interactive Learning Multimedia to Enhance Learning Motivation and Cognitive Learning Outcomes in Social Studies among Elementary School - Hilmi Alima Muktianti; Harun (Jurnal Pendidikan Indonesia, 2026)
The low motivation and learning outcomes of social studies in elementary school students indicate that the use of learning media is still not fully capable of creating an interactive, contextual, and student-centered learning experience. This condition indicates the need for digital learning media innovations that can increase student engagement more optimally in the learning process. This study aims to develop, evaluate, and test the effectiveness of interactive learning multimedia assisted by Google Sites in improving the motivation and cognitive learning outcomes of fifth-grade elementary school students. This study uses a Research and Development (R&D) approach with the Borg and Gall model. The research subjects included material experts, media experts, teachers, and elementary school students. Data were collected through interviews, observations, questionnaires, and cognitive learning outcome tests, then analyzed using quantitative descriptive and inferential techniques to interpret the level of validity, practicality, and effectiveness of the developed product. The results show that interactive learning multimedia assisted by Google Sites has a very good level of feasibility, is easy to implement in learning, and is able to significantly improve student motivation and learning outcomes. These findings imply that web-based interactive multimedia integration can create more participatory, adaptive, and meaningful learning, while strengthening digital media innovation as a strategic alternative in supporting classroom learning and students' independent learning.